5PSQ-099 Potentially inadequate MEDICATION DETECTED differently by PRISCUS, FORTA or EU(7)-PIM is associated with reduced cognitive function in multimorbid elderly patients. (24th March 2020) - Krüger, C; Schäfer, I; Von Renteln-Kruse, W; Scherer, M; Langebrake, C
Abstract : Background and importance: The population aged ≥65 years suffers multimorbidity associated with increasing use of potentially inappropriate medications (PIM). MultiCare, a longitudinal cohort study, collected data (eg, socioeconomic status, morbidities, drugs and risk factors) on 3189 multimorbid, elderly (65–85 years) patients in primary care in Germany. Aim and objectives: The aim was to compare three different PIM lists and to show the effect of PIM use on cognitive function in multimorbid elderly patients. Material and methods: Prescribed and over the counter drugs were classified using PRISCUS, FORTA (fit for the aged) and EU(7)-PIM lists. To measure cognitive function, patients performed a letter digit substitution test. A mixed effect maximum likelihood regression was performed to calculate the influence of PIM (all three lists separately) on the cognitive function of patients. Results: Patients were treated with 936 PRISCUS PIM (mean 0.3±0.58 per patient), 2152 FORTA PIM (0.9±1.03) and 4311 EU(7)-PIM (1.4±1.29). The most common PRISCUS PIM was amitriptyline (2.8%), the most common FORTA PIM was phenprocoumon (13.8%) and the most common EU(7)-PIM was omeprazole (14.0%). In patients who used seven drugs or more, significantly more PIM according to all three lists were detected. Older age (patients ≥80 years) was associated with increased use of PIM according to FORTA and PRISCUS (p=0.0052, p=0.0001). The three lists rated PIM differently, with an overall overlap of 6.6% and 18.2% (EU(7)-PIM and FORTA PIM), 9.7% (EU(7)-PIM and PRISCUS PIM) and 0.2% (FORTA and PRISCUS PIM) between two lists. The increased use of PIM was significantly associated with reduced cognitive function (all PIM lists p≤0.0001). This association was detected with a correlation coefficient of −0.72 for PRISCUS PIM, −0.60 for FORTA PIM and −0.44 for EU(7)-PIM. Conclusion and relevance: Polypharmacy was identified as a risk factor for the use of PIM. The connection of decreased cognitive function and the use of PIM underlines the importance of reducing the amount of PIM in multimorbid elderly patients. References and/or acknowledgements: No conflict of interest.